Lao PDF Economic Monitor, September 2010 Update : Managing Macroeconomic Balances to Sustain High Economic Growth - World Bank (Washington, DC, 2017)
Lao PDR economic growth continues to be strong in 2010, against the backdrop of a fragile global recovery yet dynamic regional demand. Growth is projected at 8.5 percent in 2010, from 7.5 percent in 2009. The resources sector is projected to contribute about 4 percentage points of economic growth, of which electricity, water and gas about 3.2 percentage points. This update reports mainly on recent economic developments and medium-term outlook for the country.